Memórias afetivas, processos de vida: Assunção Gonçalves artista e educadora do Cariri cearense - Ana Cláudia Lopes de Assunção (2017)
This thesis deals with the artist Assunção Gonçalves (1916-2013), from the Cariri cearense and the creation process developed from the analysis of the materials and techniques explored by the artist and their contributions in teaching / learning in the classroom. In the analysis of the works, it was sought to identify its creation process and its relations with the local culture, focusing on this process the artist's life trajectory andthe connections with its production, recognizing its style, thematic approaches, techniques and materials explored. It was tried to identify which influences that the painting of Assunção Gonçalves exerts on the local culture and in which way the artist organized and systematized its ideas and its questions to realize his paintings. In addition to her paintings, the artist is recognized as guardian of the memory of the city of Juazeiro do Norte and as Master of Culture, for the execution of her lace and her confectionery cakes, having received several honors. Experiments were done with materials and techniques worked by the artist that resulted in an artistic production that covers both thequestions, the procedures and the methodologies of the artist and the researcher. A process workbook was created where the research on painting materials and techniques is recorded. It is intended that this thesis give visibility to the life trajectory of Assunção Gonçalves, as an artist and educator, being a reference source for the teaching / learningof Art, as well as, to instigate students, teachers / artists / researchers to seek to understand The possibilities and limitations of artistic materials in the field of Painting.